Oleander poisoning in cattle - Ozgur Ozdemir; M. Kemal Ciftci; Mehmet Maden (Eurasian Journal of Veterinary Sciences)
In this case report, pathological findings in cattle poisoning that was thought to be caused by the leaves of Nerium oleander in a farm was described. Clinically, sudden death, anemia and diarrhea were seen. Post-mortem examination of the animals revealed changing degrees of hyperemia, edema, and petechial bleedings were observed. In histopathological examination, edema, hyperemia and occasional hemorrhage with degeneration and necrosis in myocytes and neurons in heart and brain were detected. Based on the pathological findings, observations of oleander leaves in the feeders and deaths after the oleander trees were cut down have verified the diagnosis of oleander poisoning in these cattle.